Inovação e responsabilidade social e o desempenho das firmas brasileiras e europeias - Santos, Andressa Ruth Sousa (2018)
The process of strategic adaptation of firms, aiming to adapt the demands of contextualization of competitiveness, attract attention to management literature, is better than the transition strategy in competitiveness and performance improvement. Given this scenario, companies must adopt competitive strategies, with a goal of success or success desired. Among these strategies, innovation and corporate social responsibility stand out. The theoretical framework of Resource Based View (RBV) is a practice and an organizational idiosyncrasy as a distinction between the companies. Thus, it is useful to have resource management and a strategy that can leverage the company's return due to differentiation. Based on the RBV, an innovation and incorporation of environmental and social laws can be carried out in a discretionary manner, with incentive to the growth of competitive benefits. In order to verify similarities and divergences between innovative and socioenvironmental activities carried out in Brazil and in developed countries, the following question is formulated: What is the relationship between innovation strategies and corporate social responsibility in the performance of companies in Brazil and Europe? In this context, the study aims to analyze the relationship between innovation strategies and corporate social responsibility in the performance of companies in Brazil and Europe. This is a descriptive research of a quantitative nature, bringing together a sample of 160 Brazilian industrial companies listed in B3 and the European industrial companies listed on the NYSE Euronext, which disseminate the necessary information for data analysis. Data were extracted from secondary sources, such as financial statements, as well as socioeconomic-financial databases, such as Thomson Reuters® and CSRhub®, totaling 686 observations. In order to reach the proposed objectives, multivariate data techniques were applied, such as Test of Differences Between Means, Logistic Regression and Multiple Linear Regression with panel data, covering the analysis of the period from 2013 to 2017. The results of the research indicate that there are significant differences in the strategies of innovation and CSR between Brazilian and European companies. As for the relationship of these strategies to business performance, only innovation when measured through the Environment Innovation indicator had an influence on the market performance of both Brazilian and European companies. When analyzing the effect of the other strategies of innovation and CSR, it was not possible to identify the existence of any relationship with performance in the joint analysis of Brazilian and European firms, suggesting that the effects of these two strategies would take a longer time to be identified. In the individual analyzes, the results were different, where R & D spending had a positive influence on the market performance of European companies, and social responsibility practices had a positive influence on the performance of operational activity in Brazilian companies and the performance of operational efficiency in companies European countries. It is concluded that in general, given its economic context, investments in innovation and CSR can be important sources of competitive advantage. However, it is necessary to point out that the results of this research present inconclusive findings about the relationship between the constructs, corroborating some national and international studies that point out the absence of the effects of innovation and CSR on corporate performance, contrary to RBV assumptions